The Administrative and Financial Reforms of Sultan al-Nasir (Case Study The Nasiri Land Survey (Rawk) of 715 AH/1315 AD): The Administrative and Financial Reforms of Sultan al-Nasir (Journal of Humanitarian and Applied Sciences, 2025)
The Nasiri Rawk was a reform initiative aimed at introducing administrative and financial amendments.It focused on revising the collection of Kharaj (land tax) on taxable lands, defining the beneficiary classes, and modifying a wide range of other taxes feeding the state treasury (Bayt al-Mal).This research examines the nature of the land survey (Rawk) during the reign of Sultan al-Nasir Muhammad ibn Qalawun, seeking to understand the resulting administrative and financial reforms and their relation to curtailing the influence of feudal lords from the amirs and soldiers. These lords controlled vast agricultural lands, exploited them, and transferred ownership of some state-owned agricultural lands to their private accounts.The Nasiri Rawk led to a series of fiscal reforms that positively impacted a broad segment of taxpayers, although this was not its primary objective. It also succeeded in tightening state control over its revenues and reaffirming the strength of its institutions, embodied in the authority of the Sultan and his Mamluks.
Keywords: The Nasiri Rawk; Sultan al-Nasir; – Taxes; Financial Reform; Administrative Reform